INTERACTION OF TRADITIONS AND INNOVATIONS IN MODERN MUSIC EDUCATION (American Journal of Pedagogical and Educational Research, 2023)
The article examines the role of traditions and innovations, and also determines the prospects of music education in the formation of a socially and professionally significant personality. The main attention is paid to the constructive nature of the unity of traditions and innovations in music education.